2010
DOI: 10.1111/j.1745-7599.2010.00489.x
|View full text |Cite|
|
Sign up to set email alerts
|

Veterans' perceptions of care by nurse practitioners, physician assistants, and physicians: A comparison from satisfaction surveys

Abstract: The VHA is the largest healthcare system and the single largest employer of NPs and PAs in the country. This study shows that a majority of the primary care clinic patients prefer to see NPs as compared with PAs and physicians. Besides clinical care, NPs focus on health promotion, disease prevention, health education, attentiveness, and counseling. Physicians and PAs should be educated on these characteristics to promote patient satisfaction and expected outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…In particular, nurse practitioners' implementation of holistic care has been identified as a key aspect of their role in the enactment of the Chronic Care Model of Disease Management; the nurse practitioners addressed the patients' concerns and barriers to adherence and arranged for access to needed services [5]. This is additionally demonstrated by their assessment and monitoring of symptoms, as well as their provision of information on the symptoms and symptom management strategies [35]; attendance to patients' educational [29], physical and psychosocial [31] needs and in getting to know patients as individuals and not just remaining content with a knowledge of the patients' disease profile alone [36]. In the present study, about half of the nurse practitioners indicated that they provide education regarding health promotion and self-management on a frequent basis, which differs from what has been reported in the literature [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, nurse practitioners' implementation of holistic care has been identified as a key aspect of their role in the enactment of the Chronic Care Model of Disease Management; the nurse practitioners addressed the patients' concerns and barriers to adherence and arranged for access to needed services [5]. This is additionally demonstrated by their assessment and monitoring of symptoms, as well as their provision of information on the symptoms and symptom management strategies [35]; attendance to patients' educational [29], physical and psychosocial [31] needs and in getting to know patients as individuals and not just remaining content with a knowledge of the patients' disease profile alone [36]. In the present study, about half of the nurse practitioners indicated that they provide education regarding health promotion and self-management on a frequent basis, which differs from what has been reported in the literature [6].…”
Section: Discussionmentioning
confidence: 99%
“…This component of PCC has been commonly assessed in terms of the extent of individualizing healthcare. Nurse practitioners have been found to provide flexible, individualized care, that is compatible with the health condition, goals and life experiences of patients with chronic illnesses [4]; to listen actively to patients' concerns and to individualize care [29,31,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are found in many areas of NP practice including hospital-based emergency departments, inpatient, and primary care settings (Bevis et al, 2008;Budzi et al, 2010;Cooper, Lindsay, Kinn, & Swan, 2002;Guzik et al, 2009;Kleinpell et al, 2008;Lin et al, 2002;Mundinger et al, 2000;Sakr et al, 1999). While studies exploring patient satisfaction with NPs in primary care abound, there is a limited number of studies evaluating patient satisfaction in the hospital setting.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…The care provided by NPs for various patient populations seems to be equivalent to the quality of care provided by medical staff (Bevis et al, 2008;Budzi et al, 2010;Guzik et al, 2009;Kleinpell et al, 2008;Mundinger, et al, 2000;Pioro et al, 2001;Sakr et al, 1999). Nurse practitioners working in emergency departments provide care for a variety of patients and have to perform numerous procedures.…”
Section: Quality Of Carementioning
confidence: 99%